THE ROLE OF THE RETAILERS IN CAUSE-RELATED MARKETING: A REFERENCE TO THE SPANISH CASE - M. Mercedes Galán - Ladero; Clementina Galera - Casquet (Ekonomski Vjesnik, 2015)
Cause-Related Marketing (CRM) is one of the most relevant Corporate Social Responsibility (CSR) initiatives nowadays. Its most important characteristic is that corporate donation is conditioned by sales, that is, CRM ultimately depends on consumer behavior. In this paper, we focus on CRM programs and its application in a specific industry: distribution sector. Thus, our aim is to understand the fundamental features or the practice of these programs in the distribution sector in Spain, to study the role played by retailers and their possible influence on the consumer behavior, so that companies can better design these campaigns and achieve greater success. Hence, the paper is organized as follows. First, we review the CRM conceptual framework in which the theoretical development of this work is based. Secondly, and from a list of companies associated to the National Association of Large Distribution Companies (ANGED), the most representative retail association in Spain, we observe the Spanish situation and analyze the main campaigns carried out by these retailers during the last years. This information was completed consulting each retailer´s website, asking them for additional information by email, and with a general internet search. After that, we present and discuss the main results, and summarize the most relevant conclusions, as well as the theoretical contribution and managerial implications. One of the most important findings shows the retailer´s influence on consumer behavior and the key role of the retailers in the success of CRM programs. Finally, we also include possible limitations and further research.